2011
DOI: 10.1016/j.neurobiolaging.2009.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Running reduces stress and enhances cell genesis in aged mice

Abstract: Cell proliferation and neurogenesis are diminished in the aging mouse dentate gyrus. However, it is not known whether isolated or social living affects cell genesis and stress levels in old animals. To address this question, aged (17–18 months old) female C57Bl/6 mice were single or group housed, under sedentary or running conditions. We demonstrate that both individual and socially housed aged C57Bl/6 mice have comparable basal cell proliferation levels and demonstrate increased running-induced cell genesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 40 publications
9
57
0
3
Order By: Relevance
“…However, the group that received voluntary exercise before stress induction presented a significantly higher number of nestin-expressing cells over the restraint stress-induced group. This result supports previous studies which found that voluntary wheel running enhanced neurogenesis in mice 35,36 . Brain-derived neurotrophic factor, IGF-1 (insulin like growth factor-1), and neurotrophin are the particular neurotrophic factors which are related to cell survival and cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…However, the group that received voluntary exercise before stress induction presented a significantly higher number of nestin-expressing cells over the restraint stress-induced group. This result supports previous studies which found that voluntary wheel running enhanced neurogenesis in mice 35,36 . Brain-derived neurotrophic factor, IGF-1 (insulin like growth factor-1), and neurotrophin are the particular neurotrophic factors which are related to cell survival and cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…An interesting contradiction exists in this respect regarding the direction of the generally positive effect of exercise on AN. Exercise is generally associated with beneficial changes, also in its effects on mood (Ernst et al 2006;Brené et al 2007;Kannangara et al 2011;Vivar et al 2013) and known to potently increase neurogenesis. Paradoxically, GCs are also increased during running.…”
Section: Stress Regulates Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…However, according to some reports, exercise can be effective in older animals and has no effect in young animals (17). Research has also found that exercise has little effect in improving memory and does not affect object recognition tasks (13).…”
Section: Introductionmentioning
confidence: 99%